THE IMPORTANCE OF PRODUCT QUALITY, PRICE CONSCIOUSNESS, CUSTOMER VALUE AND BRAND IMAGE TOWARDS PT SOPHIE PARIS INDONESIA’S REPURCHASE INTEREST WHICH INTERVENED BY ATTITUDE VARIABLES - Solihin, Rajes; Imaningsih, Erna Sofriana (Dinasti International Journal of Management Science, 2021)
This research has purposes to explore the effects caused by product quality, price consciousness, customer value, brand image towards repurchase intention to PT Sophie Paris Indonesia products which are mediated by attitude variable. This research form used a quantitative method with the type of research included in causal research. The research population is consumers who have purchased Sophie Paris products in DKI Jakarta. The sampling technique used purposive with a total sample of 240 people. Data collection techniques by surveys through questionnaires and SEM method analyzed which processed by the SmartPLS 3.0 application. The findings viewed that partially product quality, price consciousness, customer value and brand image had a positive and significant involvement in attitudes towards the brand, which also affected the repurchase intention of Sophie Paris products. The variable that has the strongest impact is price consciousness on brand attitudes so that this highly affects the repurchase interest towards Sophie Paris products.